ANALISIS FAKTOR YANG MEMPENGARUHI PENGGUNAAN ALAT TRANSPORTASI OLEH MAHASISWA FAKULTAS TEKNOLOGI LINGKUNGAN DAN MINERAL UNIVERSITAS TEKNOLOGI SUMBAWA - Yogi Mahesa; Eti Kurniati; Adi Mawardin; Hermansyah (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
Since 2020 the number of students at the Faculty of Environmental and Mineral Technology (FTLM), Sumbawa University of Technology (UTS) has increased, and along with the increase in the number of students, it will affect the growth of transportation users. This study aims to analyze the factors that influence FTLM students in using transportation, in this case, FTLM students choose to use private motorcycle vehicles. Data collection using questionnaires and field observations on 86 respondents taken based on random sampling techniques. The data were analyzed using the binary logistic regression method. This method has four model tests, namely assessing the overall model (Overall Model Test), testing the feasibility of the model (Goodness Fit Test), the coefficient of determination and the classification matrix. The results showed that there are 2 factors or variables that are the reasons for FTLM students to use private motorcycle vehicles, namely vehicle ownership and distance to campus.